2015
DOI: 10.1080/01634372.2015.1019657
|View full text |Cite
|
Sign up to set email alerts
|

Economic Well-Being Among Older-Adult Households: Variation by Veteran and Disability Status

Abstract: This analysis uses data from the Survey of Income and Program Participation (SIPP) to examine whether veteran and disability statuses are jointly associated with household-level poverty and material hardship among older adults. Compared to households that do not include a person with a disability or veteran, disabled non-veteran households are more likely to be in poverty and to experience home hardship, medical hardship, and bill-paying hardship. Disabled veteran households are not significantly different in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…Specifically, those who enlisted after the shift to an all-volunteer force rank less favourably than their non-veteran peers in terms of socio-economic status, educational attainment (29) and the presence of behavioural health problems (29)(30)(31)(32) , all of which are hypothesized to account for the increased risk of adverse social (33,34) and economic (35) outcomes. Two previous studies of material hardship examined whether household food insufficiency (a more limited measure of food hardship available in the Survey of Income and Program Participation) varied by the presence of veteran and disability status (36,37) . In comparison to households with no veterans and no disabled residents, the first study found that the odds of food insufficiency were significantly higher among disabled veteran households and the second found higher odds of food insufficiency among older adult households with disabled veterans and those with non-disabled veterans (36,37) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, those who enlisted after the shift to an all-volunteer force rank less favourably than their non-veteran peers in terms of socio-economic status, educational attainment (29) and the presence of behavioural health problems (29)(30)(31)(32) , all of which are hypothesized to account for the increased risk of adverse social (33,34) and economic (35) outcomes. Two previous studies of material hardship examined whether household food insufficiency (a more limited measure of food hardship available in the Survey of Income and Program Participation) varied by the presence of veteran and disability status (36,37) . In comparison to households with no veterans and no disabled residents, the first study found that the odds of food insufficiency were significantly higher among disabled veteran households and the second found higher odds of food insufficiency among older adult households with disabled veterans and those with non-disabled veterans (36,37) .…”
mentioning
confidence: 99%
“…Two previous studies of material hardship examined whether household food insufficiency (a more limited measure of food hardship available in the Survey of Income and Program Participation) varied by the presence of veteran and disability status (36,37) . In comparison to households with no veterans and no disabled residents, the first study found that the odds of food insufficiency were significantly higher among disabled veteran households and the second found higher odds of food insufficiency among older adult households with disabled veterans and those with non-disabled veterans (36,37) . However, these two studies were limited by a focus on food insufficiency only, which is much rarer than FI and based only on a single survey item.…”
mentioning
confidence: 99%
“…This represents a significant omission considering recent evidence that poverty and material hardship, including food insufficiency, are experienced in many households that include disabled, and to a lesser extent, nondisabled veterans (Heflin et al 2012;London et al 2011;Wilmoth et al 2015). Other research also indicates high rates of food insecurity among veterans of Iraq and Afghanistan; specifically, one in four veterans reported past-year food insecurity in 2001, and 12 % reported very low food security (Widome et al 2014).…”
Section: Previous Literaturementioning
confidence: 76%
“…The 5-year (2008-2012) public-use ACS file that we analyzed did not contain measures of disability. Given that prior research indicates that households that include a disabled veteran are at a much higher risk of poverty and all forms of material hardship, including food insecurity, than are households that include a nondisabled veteran (Heflin et al 2012;London et al 2011;Wilmoth et al 2015), this is a serious limitation that should be addressed in future research. Future research should also focus specifically on the transition from active-duty to veteran status in order to better understand how, why, and with what consequences the loss of foodrelated resources during this dynamic period occurs.…”
Section: Discussionmentioning
confidence: 94%
“…Recent research indicates that at age 40, veterans who served on active duty during the era of the All-Volunteer Force (which began when conscription ended in 1973) report poorer self-rated health, even after controlling for a range of covariates, including socioeconomic status and health behaviors (Teachman 2011). The higher rates of poor health, functional limitation, and disability among veterans during midlife may contribute to health disparities in later life by influencing the economic well-being of veteran families; recent research indicates that households containing disabled veterans experience an increased risk of poverty and material hardship (Heflin et al 2012;London et al 2011;Wilmoth et al 2015).…”
Section: Military Service and Physical Healthmentioning
confidence: 99%